Anterior cruciate ligament reconstruction: the role of lateral posterior tibial slope as a potential risk factor for failure - Di Benedetto, Paolo; Buttironi, Michele Mario; Mancuso, Francesco; Beltrame, Alessandro; Gisonni, Renato; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the workAnterior cruciate ligament (ACL) reconstruction is an extremely frequent surgery. The analysis of anatomical factors is becoming increasingly important and the study of clinical, arthroscopic and radiological methods to evaluate and understand them aims to positively affect the patient's outcome. This work aims to analyze the role of Lateral Posterior Tibial Slope (LPTS) as a potential risk factor for ACL reconstruction failureMaterials and MethodsAt the Clinic of Orthopedic of Udine, between November 2018 and August 2020, 47 revisions of the ACL were performed. We analyzed MRI scans with particular attention to the LPTS. Patient images were analyzed by a single senior orthopedic surgeon who was blinded to patient history, age and gender.ResultsComparing with a value reported in literature as normal (LPTS estimated 6.5°) we see how the difference between the average LPTS values ​​in the sample is significantly higher than the normal values ​​(P